Considerations on the impact of experiments and computational simulations with gravitational waves on the advancement of physics: the context of LIGO - Almeida, Pamella Aline; Magalhães, Nadja (Cadernos de Astronomia, 2026)
The direct detection of gravitational waves represents one of the most important achievements of contemporary physics, opening a new window for observing the Universe. This work presents a report of a personal experience related to the scientific impact of gravitational-wave experiments regarding the experimental practice acquired through activities related to the Laser Interferometer Gravitational-Wave Observatory (LIGO) during a scientific exchange at the University of California, Riverside (UCR). As well, the computational simulation practice associated with the master’s research project of one of the authors is presented. Various experimental activities are described, like those involving standard LIGO cleaning protocols, the assembly and sealing of a vacuum chamber for preliminary tests, studies on heat absorption using spherical mirror configurations, and materials analysis. Based on the experience acquired, the authors reflect that matching experimental practice and computational simulation is valuable to help understand instrumental limitations, mitigating noise sources, and improving devices applied to gravitational-wave detection.
Keywords: Experience report; Gravitational Waves; LIGO